Isothermal B2 → B19′ martensitic transformation in Ti40.7Hf9.5Ni44.8Cu5 shape memory alloy. (February 2016) - Resnina, N.; Belyaev, S.; Shelyakov, A.
Abstract: Isothermal martensitic transformation from cubic B2 phase to monoclinic B19′ phase is observed by calorimetric measurement at a constant temperature that is higher than the start temperature of the forward martensitic transformation found during continuous cooling. The dependences of the alloy volume undergone the forward transformation under isothermal condition on the holding temperature and time are obtained. It is assumed that the realization of the phase transformation under isothermal conditions is caused by a relaxation of elastic energy accumulated in the sample due to the formation of quasi-static strain nanodomains. Graphical abstract: